A PERFORMATIVE APPROACH TO WOMEN AND POWER DURING THE ROMAN REPUBLIC - Ferrer-Alcantud, Coré (POTESTAS. Estudios del Mundo Clásico e Historia del Arte, 2018)
The objective of this paper is to investigate the involvement that women in Republican Rome could have had in matters alleged to be enjoyed exclusively by men, concerns such as politics and finances, with the ulterior aim of revealing actual social realities, formerly ignored and disregarded. Previous studies focused largely on women’s domesticity, fertility, and the preservation of a stainless behavior as a result of the exempla outlined by ancient authors such as Livy, Vergil, Plutarch, and Appian, male writers who lived on the edge of time between the precepts of the Republic and the brand-new outset of the Principate. By using an innovative approach based on Judith Butler’s performativity, we will be able to explore Roman women’s identities and their closeness to an actual but traditionally obscured power.